IWF Anti-Doping Policy - Draft (2004)
DEFINITION OF DOPING ANTI-DOPING RULE VIOLATIONS PROOF OF DOPING THE PROHIBITED LIST TESTING DOPING CONTROLS AT COMPETITIONS COLLECTION OF URINE SAMPLES AT COMPETITIONS COLLECTION OF URINE SAMPLES AT UNANNOUNCED TESTING BLOOD COLLECTION SAMPLE PROCEDURE ANALYSIS OF SAMPLES RESULTS MANAGEMENT RIGHT TO A FAIR HEARING PRINCIPLES FOR A FAIR HEARING AUTOMATIC DISQUALIFICATION OF INDIVIDUAL RESULTS SANCTIONS ON INDIVIDUALS SANCTIONS AND COSTS ASSESSED AGAINST NATIONAL FEDERATIONS APPEALS NATIONAL FEDERATIONS INCORPORATION OF IF RULES, REPORTING AND RECOGNITION RECOGNITION OF DECISIONS BY OTHER ORGANISATIONS STATUTE OF LIMITATIONS IWF COMPLIANCE REPORTS TO WADA AMENDMENT AND INTERPRETATION OF ANTI-DOPING RULES APPENDIX 1 - DEFINITIONS APPENDIX 2 - ACKNOWLEDGEMENT OF AGREEMENTS APPENDIX 3 - SPECIFIC REQUIREMENTS FOR THE IWF DOMPNG CONTROLS